Competing priorities that rival health in adults on probation in Rhode Island: substance use recovery, employment, housing, and food intake - Kimberly R. Dong; Aviva Must; Alice M. Tang; Curt G. Beckwith; Thomas J. Stopka (BMC, 2018)
Abstract Background Individuals on probation experience economic disadvantage because their criminal records often prohibit gainful employment, which compromises their ability to access the basic components of wellbeing. Unemployment and underemployment have been studied as distinct phenomenon but no research has examined multiple determinants of health in aggregate or explored how these individuals prioritize each of these factors. This study identified and ranked competing priorities in adults on probation and qualitatively explored how these priorities impact health. Methods We conducted in-depth interviews in 2016 with 22 adults on probation in Rhode Island to determine priority rankings of basic needs. We used Maslow's hierarchy of needs theory and the literature to guide the priorities we pre-selected for probationers to rank. Within a thematic analysis framework, we used a modified ranking approach to identify the priorities chosen by participants and explored themes related to the top four ranked priorities. Results We found that probationers ranked substance use recovery, employment, housing, and food intake as the top four priorities. Probationers in recovery reported sobriety as the most important issue, a necessary basis to be able to address other aspects of life. Participants also articulated the interrelatedness of difficulties in securing employment, food, and housing; these represent stressors for themselves and their families, which negatively impact health. Participants ranked healthcare last and many reported underinsurance as an issue to accessing care. Conclusions Adults on probation are often faced with limited economic potential and support systems that consistently place them in high-risk environments with increased risk for recidivism. These findings emphasize the need for policies that address the barriers to securing gainful employment and safe housing. Interventions that reflect probationer priorities are necessary to begin to mitigate the health disparities in this population.